2012
DOI: 10.1161/circep.112.972307
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Modulation

Abstract: A variety of experimental and clinical reports have engendered a different approach to cardiac arrhythmias as well as other cardiovascular conditions. The focus of a new paradigm is the autonomic nervous system and its important role in various pathological states. From an overall standpoint, this new paradigm can be encompassed by the term "autonomic modulation," which would include autonomic nerve stimulation or autonomic denervation to modulate the autonomic activity in physiological or pathophysiological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Autonomic modulation stands apart from alternative atrial fibrillation treatments by centering on the autonomic nervous system's role in driving and perpetuating cardiac arrhythmias, particularly atrial fibrillation [92,94]. Experimental models, such as vagal activation, offer insights into neural mechanisms and the impact of neuromodulation, evident in its ability to limit infarct size and protect against ventricular arrhythmias during myocardial infarction [97]. These models facilitate a deeper understanding of neural mechanisms and the effects of autonomic modulation [98].…”
Section: Autonomic Modulation In Atrial Fibrillation Managementmentioning
confidence: 99%
“…Autonomic modulation stands apart from alternative atrial fibrillation treatments by centering on the autonomic nervous system's role in driving and perpetuating cardiac arrhythmias, particularly atrial fibrillation [92,94]. Experimental models, such as vagal activation, offer insights into neural mechanisms and the impact of neuromodulation, evident in its ability to limit infarct size and protect against ventricular arrhythmias during myocardial infarction [97]. These models facilitate a deeper understanding of neural mechanisms and the effects of autonomic modulation [98].…”
Section: Autonomic Modulation In Atrial Fibrillation Managementmentioning
confidence: 99%
“…The properties of the atrial wall and may be identified by changes in the spectrum as "AF Nests" [22][23][24][25] (this name resulted from its relation with the AF physiopathology as they present electrical resonance 26,27 favoring the AF maintenance).…”
Section: Rf Catheter Ablation For Vagal Denervationmentioning
confidence: 99%
“…49,50 In contrast to pharmacological therapy and pacemaker implantation, GP ablation for vasovagal syncope provides a means of targeting the root of the problem, which includes disturbances of the intrinsic CANS. 51 GP ablation for vasovagal syncope was first introduced by Yao et al, who reported their initial experience on 10 patients with highly symptomatic vasovagal syncope. 52 Selective highfrequency stimulation-guided GP ablation resulted in an impressive amelioration of their prodromal symptoms and no recurrence of syncope over 30 months of follow up.…”
Section: Gp Ablation For Vasovagal Syncopementioning
confidence: 99%